Concurrent macular oedema and optic neuritis in Crohn’s disease with varied response to steroids - Malik, Adeela (BMJ Publishing Group, 2010)
A patient with a 10-year history of Crohn’s disease presented to our ophthalmology service with symptoms of acute anterior uveitis. Previous episodes had been treated successfully with topical steroids. However, on this occasion after treatment with topical steroids, the patient developed macular oedema with concurrent optic neuritis in the affected eye. Furthermore, optic neuritis persisted despite oral steroid treatment contrary to expectations based on current literature. After 6 months of treatment, optic disc oedema had markedly improved but was replaced by sectoral disc pallor.